2007
DOI: 10.1358/mf.2007.29.9.1116315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooling on histamine-induced contractions of human umbilical artery: The role of ion channels

Abstract: The effects of cooling (to 28 degrees C) on histamine (10(-9) - 3 x 10(-4) M)-induced contractions and the role of calcium (Ca(2+)), potassium (K(Ca) (2+)) and sodium (Na(+)) channel blockers in the cooling-induced responses were investigated in the endothelium-denuded human umbilical artery. Concentration-response curves to histamine were isometrically recorded at 37 and 28 degrees C (control). The same procedure was repeated at 28 degrees C in the presence of tetraethylammonium (TEA, 10(-3) M), pilsicainide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our findings demonstrate that sevoflurane produced vasodilation, at least in part, via an effect on the sarcolemmal voltage-operated calcium channel (VOCC). Prior incubation with the VOCC channel blocker verapamil, at concentrations similar to that previously reported [ 17 , 18 ], significantly inhibited sevoflurane-mediated vasodilation of the pre-constricted chorionic plate arterial rings. These findings demonstrate that sevoflurane-mediated vasodilation in this circulation is dependent in part on a blocking effect at the VOCC channel.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings demonstrate that sevoflurane produced vasodilation, at least in part, via an effect on the sarcolemmal voltage-operated calcium channel (VOCC). Prior incubation with the VOCC channel blocker verapamil, at concentrations similar to that previously reported [ 17 , 18 ], significantly inhibited sevoflurane-mediated vasodilation of the pre-constricted chorionic plate arterial rings. These findings demonstrate that sevoflurane-mediated vasodilation in this circulation is dependent in part on a blocking effect at the VOCC channel.…”
Section: Discussionsupporting
confidence: 81%
“…Series 3 examined the role of the sarcolemmal voltage-operated Ca ++ channel (VOCC). Following U46619 pre-constriction, verapamil 1 × 10 -6 M, which specifically blocks the VOCC channel [ 9 , 17 , 18 ] or vehicle was added, and the rings exposed to sevoflurane or perfusing gas alone as described for series 1A. Series 4 examined the role of the sarcolemmal voltage-independent Ca ++ channels (VICC) [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…This was supported by Atalik et al. who also concluded that the endothelium had no role in temperature‐induced responses in the rabbit aorta, calf coronary artery and human umbilical artery. However, in contrast to these observations, it has been shown that cooling decreased sensitivity of the rabbit ear artery to stimulation by histamine and endothelin‐1 by increasing the release of NO.…”
Section: Discussionmentioning
confidence: 69%
“…In their studies, Mustafa and Thulesius 15,18 concluded that coolinginduced relaxation of the rat pulmonary artery and rabbit carotid artery was independent of the vascular endothelium as cooling induced relaxation in artery segments with and without endothelium. This was supported by Atalik et al 35,36 who also concluded that the endothelium had no role in temperature-induced responses in the rabbit aorta, calf coronary artery and human umbilical artery. However, in contrast to these observations, it has been shown that cooling decreased sensitivity of the rabbit ear artery to stimulation by histamine 14 and endothelin-1 37 by increasing the release of NO.…”
Section: Effect Of Pvat On the Anticontractile Effect Of Coolingmentioning
confidence: 70%
“…Notably, umbilical vessels play a vital role in feto-placental circulation [ 9 ]. Due to lack of autonomic innervation, vessel tone of human umbilical vessels is mainly regulated by vasoactive substances released locally or carried by the blood stream, such as histamine [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%